2016
DOI: 10.2174/1874192401610010001
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Cardiovascular Disease

Abstract: Cardiovascular disease [CVD] is a leading cause of mortality accounting for a global incidence of over 31%. Atherosclerosis is the primary pathophysiology underpinning most types of CVD. Historically, modifiable and non-modifiable risk factors were suggested to precipitate CVD. Recently, epidemiological studies have identified emerging risk factors including hypotestosteronaemia, which have been associated with CVD. Previously considered in the realms of reproductive biology, testosterone is now believed to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
1
10
0
1
Order By: Relevance
“…Epidemiological studies identified TD as a risk factor for CVD. 88 Furthermore, TTh improves CBV perfusion and improves mood in men with TD and low T levels predict a poor CV risk profile. 89 , 90 We should point out that we made no attempts to monitor changes in lifestyle, simply because when this registry study was initiated, there was no expectation that men would lose weight, lose WC, and experience improvement in lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies identified TD as a risk factor for CVD. 88 Furthermore, TTh improves CBV perfusion and improves mood in men with TD and low T levels predict a poor CV risk profile. 89 , 90 We should point out that we made no attempts to monitor changes in lifestyle, simply because when this registry study was initiated, there was no expectation that men would lose weight, lose WC, and experience improvement in lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…24 The Leydig cells, which are located between the seminiferous tubules of the testis, are responsible for the synthesis and secretion of testosterone. 24 The Leydig cells, which are located between the seminiferous tubules of the testis, are responsible for the synthesis and secretion of testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that testosterone is essential for multiple physiological pathways including male secondary sexual development and fertility. 24 The Leydig cells, which are located between the seminiferous tubules of the testis, are responsible for the synthesis and secretion of testosterone. [25][26][27] Several studies have reported that dietary factors such as high-fat diets and high-calorie diets could inhibit Leydig cell steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that males with low levels of testosterone were prone to cardiovascular diseases [14, 15]. Furthermore, low levels of endogenous testosterone are directly linked to male infertility, erectile dysfunction and oligospermia.…”
Section: Testosterone and Its Functionsmentioning
confidence: 99%